2011
DOI: 10.1371/journal.pntd.0001011
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Schistosome Tegumental Alkaline Phosphatase (SmAP)

Abstract: Schistosomes are parasitic platyhelminths that currently infect over 200 million people globally. The parasites can live for years in a putatively hostile environment - the blood of vertebrates. We have hypothesized that the unusual schistosome tegument (outer-covering) plays a role in protecting parasites in the blood; by impeding host immunological signaling pathways we suggest that tegumental molecules help create an immunologically privileged environment for schistosomes. In this work, we clone and charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(75 citation statements)
references
References 53 publications
2
72
0
1
Order By: Relevance
“…We noted two patterns of immunogold particle localization-clustered and scattered-in the tegument. While scattered immunogold particles have been seen in other immunolocalization experiments involving tegumental molecules (4,16,17), the report of the clustered pattern presented here is, to our knowledge, unique. We speculate that the clustered particles overlay membranous bodies within the tegument called multilaminate vesicles (MLV).…”
Section: Discussionsupporting
confidence: 47%
“…We noted two patterns of immunogold particle localization-clustered and scattered-in the tegument. While scattered immunogold particles have been seen in other immunolocalization experiments involving tegumental molecules (4,16,17), the report of the clustered pattern presented here is, to our knowledge, unique. We speculate that the clustered particles overlay membranous bodies within the tegument called multilaminate vesicles (MLV).…”
Section: Discussionsupporting
confidence: 47%
“…The GPIanchored ADP-ribosyl cyclase enzyme also on the external surface, whilst apparently unable to generate cyclic adenosine diphosphate ribose, may catabolize extracellular NAD(þ) to prevent its use by host enzymes that facilitate immune responses [50]. It has also been suggested that the adenosine generated from adenosine monophosphate by tegumental alkaline phosphatase acts as a localised immunosuppressant [51]. Lastly, the tegumental phosphodiesterase, SmNPP-5, has actually been directly implicated as a virulence factor by the use of RNAi treatment to suppress gene expression in parasites, followed by demonstration of their greatly reduced ability to establish after administration to mice [1].…”
Section: The Tegument and Immune Evasionmentioning
confidence: 99%
“…Accordingly, schistosomes may prevent their hosts from focusing immunological mediators in their vicinity [82]. In support of this notion, RNAi of adult tegumental alkaline phosphatase (SmAP) prevented production of the anti-inflammatory adenosine from an exogenously added precursor (AMP) [83]. …”
Section: Functionally Exploring Comparative Genomic Outputs: Revisitimentioning
confidence: 99%